Near-field electric field limit for radiated emission pre-compliance - Tolentino, Adrian M.; Escoto, Miguel T. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Concerning radiated emission of electronic devices, pre-compliance test methods are used as preliminary checks to standard radiated emission compliance. They do not require semi anechoic chambers or open area test sites and they give more insight to the problems encountered when the product prototype fails the test. Near-field scanning has recently been used for pre-compliance testing of radiated emission of electronic devices and shows advantages over other pre-compliance test methods. A near magnetic field limit has already been proposed for pre-compliance testing using near-field scanning. However, electromagnetic fields can become weakly magnetic at near-field. When they do, the near magnetic field limit may fail as near-field limit. In this work, near electric field limits are derived and used for pre-compliance testing. Computer simulations of a 500 terminated straight microstrip transmission line, an infinitesimal dipole, a rectangular patch microstrip antenna, and a short terminated loop inicrostrip transmission line showed that pre-compliance testing can be done with near electric field limits proposed. Cases where the limits proposed as less stringent than the magnetic near field limit have been shown. Pre-compliance testing using the near field limits was done to an actual 5002 terminated straight microstrip transmission line. Experiment and simulation showed similar results.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Electromagnetic interference; Electromagnetic compatibility